2016
DOI: 10.1155/2016/1280236
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Electrode Morphology Evolution in High Energy Density Nickel-Zinc Batteries

Abstract: Prismatic Nickel-Zinc (NiZn) batteries with energy densities higher than 100 Wh kg −1 were prepared using Zn electrodes with different initial morphologies. The effect of initial morphology of zinc electrode on battery capacity was investigated. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) reveal that initial morphology of zinc electrode changes drastically after a few charge/discharge cycles regardless of initial ZnO powder used. ZnO electrodes prepared using ZnO powders synthesized from ZnC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Similar to samples A, the weak peaks of calcium zincate are detected in all samples B. It can be concluded that is no difference between all zinc electrodes after third discharge and electrode paste before first charge, and the result corresponds to previous report in the literature [32]. …”
Section: Xrd Patterns Analysis Of Zinc Electrodessupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to samples A, the weak peaks of calcium zincate are detected in all samples B. It can be concluded that is no difference between all zinc electrodes after third discharge and electrode paste before first charge, and the result corresponds to previous report in the literature [32]. …”
Section: Xrd Patterns Analysis Of Zinc Electrodessupporting
confidence: 88%
“…Also, the commercial ZnO showed a wide range of particle size distribution with most of the particles having needle-like shapes as well as having tripod and nanorod shapes [32].…”
Section: The Characterization Of Zinc Oxide Powdermentioning
confidence: 99%
See 1 more Smart Citation
“…Although PEO is water soluble, it is insoluble in strong alkaline media such as concentrated KOH solution. PTFE is highly hydrophobic, chemically stable, and has been used in rigid batteries including Ni‐Zn,, Li‐O 2 and MnO 2 ‐Zn . In this study, PEO and PTFE were tested and compared as binding additives.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PTFE does not dissolve in aqueous electrolytes thus avoiding electrode disintegration. These properties make PTFE a potential electrode binder ,. The objective of this research is to develop flexible electrodes by facile mixing of ingredients and study different binders.…”
Section: Introductionmentioning
confidence: 99%